Decision frameworks and the investment in R&D. (May 2015) - Baker, Erin; Olaleye, Olaitan; Aleluia Reis, Lara
Abstract: In this paper we provide an overview of decision frameworks aimed at crafting an energy technology Research & Development portfolio, based on the results of three large expert elicitation studies and a large scale energy-economic model. We introduce importance sampling as a technique for integrating elicitation data and large IAMs into decision making under uncertainty models. We show that it is important to include both parts of this equation – the prospects for technological advancement and the interactions of the technologies in and with the economy. We find that investment in energy technology R&D is important even in the absence of climate policy. We illustrate the value of considering dynamic two-stage sequential decision models under uncertainty for identifying alternatives with option value. Finally, we consider two frameworks that incorporate ambiguity aversion. We suggest that these results may be best used to guide future research aimed at improving the set of elicitation data. Highlights: We introduce a new technique for integrating probability distributions with large scale IAMs. We find that investment in energy technology R&D is important with or without a climate policy. We illustrate the importance of considering two-stage problems under uncertainty. Prospects for technological change and economic interactions must both be taken into consideration when crafting R&D policy.